Self-medication in young people in the context of COVID-19 - Rodriguez Cruz, Lisseth Dolores (2021)
Self-medication is a latent problem in our society. It is the own initiative or decision to take drugs, the consumption of drugs regardless of their origin, or medical prescription1,2. This has been increasing and has become a phenomenon that is highly studied by researchers. Thus, in pre-pandemic times, self-medication was a considerable problem in several countries, although with differences between countries in Europe and Latin America. So we have, in Spain3; The National Health System announced that in 2017 15.3% of people self-medicate. Also, in Mexico4; 86% consume medications without a doctor's prescription.